Effect of Artemisia vulgaris Extract on P53 Expression and Caspase-8 Expression (Study on Adenocarcinoma Mammae C3H Mice Given Adriamycin- Cyclophosphamide Chemotherapy Regimen) - Sugiharto, Jonathan; Hardian; Selamat Budijitno (Biomedical Journal of Indonesia, 2021)
Background: The incidence of breast cancer worldwide is still high. Surgery remains the top choice with other modalities of chemotherapy. radiation. and immunotherapy such as Artemisia vulgaris (AV). Purpose : The study was aimed to demonstrate that administration of AV extract increased the levels of p53 and Caspase-8 in adenocarcinoma mammae. Methods: This study used "Post test only control group design" on 24 females C3H mice that were randomly selected and divided into four groups : group K (control). P1 (chemotherapy). P2 (extract). and P3 (combination). Adenocarcinoma mammae comes from the inoculation of donor mice. Chemotherapy of Adriamycin 0.18 mg and Cyclophosphamide 1.8 mg were given in 2 cycles. AV 13 mg (0.2 ml) was given once daily orally. P53 and Caspase-8 levels were evaluated by imunohistochemical staining. Results: Mean of p53 and Caspase-8 levels were found in groups K. P1. P2. P3 were 22.06+1.73. 37.16+1.20. 24.60+1.08. 39.78+1.19 dan 17.16+1.28. 26.20+1.11. 24.60+1.08. 39.78+1.19. The statistical analysis showed that there were significant differences in the levels of p53 between groups of K vs P1. P3 (p=0.001). K vs P2 (p=0.048). P1 vs P2 (p=0.001). P1 vs P3 (p=0.039). P2 vs P3 (p=0.001). and in Caspase-8 between groups of K vs P1. P3 (p=0.001). K vs P2 (p=0.048). P1 vs P2 (p=0.001). P1 vs P3 (p=0.039). P2 vs P3 (p=0.001). Correlation analysis between p53 and Caspase-8 showed significant correlation (p=0.047 dan r=0.883). Conclusion: Artemisia vulgaris can improve the effectivity of Adriamycin- Cyclophosphamide chemotherapy on C3H mice with adenocarcinoma mammae in terms of elevated levels of P53 and Caspase-8.